2016
DOI: 10.17957/ijab/15.0144
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Analysis of Safflower (Carthamus tinctorius) Accessions from Different Geographic Origins using ISSR Markers

Abstract: Safflower (Carthamus tinctorius) is an oilseed crop with high quality vegetable seed oil. A set of 55 accessions from different geographical origins were introduced to constitute a breeding program germplasm. These materials were characterized by inter-simple sequence repeat (ISSR) as a simple method to reveal polymorphism among them. ISSR analysis was carried out with 13 primers. After agarose gels analysis, ISSR banding patterns were converted into binary data of presence-non presence and matrices were proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
10
3
Order By: Relevance
“…The PIC was found higher (0.48) in this work than in the findings by Ambreen et al [12], Ambreen et al [13], Barati and Arzani [49], Derakhshan et al [50], Hamdan et al [33], and Lee et al [17], all of whom used SSR markers to evaluate the genetic diversity in safflower. In their works, Houmanat et al [51] found lower PIC value of 0.23 relative to this study, using ISSRs markers in safflower. These results clearly suggest that more diverse iPBS-retrotransposon markers loci can be identified and effectively used as a tool for assessing genetic diversity and other investigations relying on genetic variants.…”
Section: Discussioncontrasting
confidence: 64%
“…The PIC was found higher (0.48) in this work than in the findings by Ambreen et al [12], Ambreen et al [13], Barati and Arzani [49], Derakhshan et al [50], Hamdan et al [33], and Lee et al [17], all of whom used SSR markers to evaluate the genetic diversity in safflower. In their works, Houmanat et al [51] found lower PIC value of 0.23 relative to this study, using ISSRs markers in safflower. These results clearly suggest that more diverse iPBS-retrotransposon markers loci can be identified and effectively used as a tool for assessing genetic diversity and other investigations relying on genetic variants.…”
Section: Discussioncontrasting
confidence: 64%
“…Genetic diversity characterization within safflower gene pools is vital for its development and improvement. Our results about mean polymorphism (93.844%) was higher to that of Houmanat et al (2016), as they found mean polymorphism of 63.38% using ISSR markers evaluating a safflower set of 55 accessions. Similarly, Golkar et al (2011) reported lower polymorphism (70%) than ours using ISSR markers.…”
Section: Discussioncontrasting
confidence: 59%
“…They evaluated 25 safflower accessions using 13 ISSR markers. Moreover, Houmanat et al (2016) revealed lower PIC value (0.23) than us using ISSR markers in safflower. The presence of higher number of effective alleles revealed the availability of maximum level of genetic diversity and is always desirable.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Understanding and mastering crop genotype is the premise for the scientific research and breeding of new hybrids. Currently, the main method to study plant quantitative traits is drawing genetic linkage map using different molecular markers and proper segregation populations (Houmanat et al, 2016;Wang et al, 2017). However, there are some shortages about genetic linkage mapping, including difficult in constructing appropriate segregating population in short time, and only could involve two allele loci.…”
Section: Introductionmentioning
confidence: 99%